Analisis Pengaruh Variasi Waktu Perlakuan Alkalisasi KOH (Kalium Hidroksida) Terhadap Sifat Mekanik Serat Tunggal Purun Tikus (Eleocharis Dulcis) - Akhmad Syarief; Iphan Fitrian Radam; Muhammad Nizar Ramadhan; Akhmad Ghiffary Budianto; Fadliyanur; Aulia Aufa Ramdhasari (Universitas Muhammadiyah Metro, 2026)
The utilization of purun tikus (Eleocharis dulcis) fiber as a reinforcement material for composites has considerable potential due to its high cellulose content. However, the hydrophilic nature of this fiber limits its interfacial bonding with the matrix, thus requiring chemical treatment to enhance its performance. This study aims to analyze the effect of varying alkali treatment durations using KOH solution on the mechanical properties of single purun tikus fibers. The alkali treatment was conducted by immersion for 3, 6, 9, and 12 hours. Mechanical tests included tensile and pull-out tests to evaluate tensile strength, elongation, elastic modulus, and interfacial shear strength (IFSS). The results showed that treatment for 3 hours provided the most significant improvement, with tensile strength reaching 75.25 MPa, elastic modulus of 12,137.5 MPa, and IFSS of 13.78 MPa. This improvement is attributed to the removal of lignin and hemicellulose, which enhanced fiber–matrix interfacial bonding. Conversely, longer treatment durations led to cellulose degradation and decreased mechanical performance. Therefore, the optimum alkali treatment duration using KOH for purun tikus fibers is 3 hours, which yields maximum improvements in mechanical strength and interfacial bonding quality.